WTO and fisheries: has Kenya really partaken?. (1st January 2013) - K'Omolo, Erick
The question of less advanced countries participation at the WTO has been much debated in recent years. The ongoing fisheries negotiation is one such area where the role of less advanced countries promises to be crucial in influencing the framework of a future discipline. Already the Doha and Hong Kong Ministerial mandates gave sufficient impetus for less advanced countries involvement by reiterating the centrality of fisheries to their economies and directing speedy discussions respectively. Although fisheries negotiation has progressed comparatively faster than other items on the table at Doha, no consensus is on sight yet while reports of declining stocks in the less advanced countries is abound. The essay, as part of an ongoing research, evaluates how and what contribution less advanced countries have made in shaping fisheries negotiation. It focuses on Kenya as part of this group by retracing her position, if any, on fisheries in both GATT and WTO. Two preliminary conclusions are made. First that though fisheries have undoubtedly been important to Kenya's economy, her trade policy in the sector is vague. Finally, it is observed that Kenya has abandoned an initial unilateral approach to negotiations for a more collegial approach.